Using Sr[Mg3SiN4]Eu2+ phosphor for enhancing color uniformity and luminous efficacy of the 7000 K IPP-WLEDs - Van-Duc Phan; Phu Tran Tin; Minh Tran; Tran Thanh Trang (Institute of Advanced Engineering and Science, 2020)
As a novel class of inorganic phosphors, oxynitride and nitride luminescent materials have received considerable attention because of their potential applications in solid-state lightings and displays. In this paper, we built the simulation model of the 7000 K in-cup phosphor packaging white LEDs (IPP-WLEDs) by using the Light Tools software. After that, the effect of the Sr[Mg3SiN4]Eu2+ phosphor particle’s size on the lighting performance in term of CCT Deviation (D-CCT), Color Rendering Index (CRI), Color Quality Scale (CQS), and Lumen Output (LO) is analyzed and investigated. In addition, the scattering processes in the phosphor layers of the 7000 K IPP_WLEDs is derived using Mat Lab software. From the research results, we can state that the phosphor size significantly effects on the lighting performance of the 7000K IPP_WLEDs. It can be seen that Sr[Mg3SiN4]Eu2+ phosphor can be considered as a novel solution for improving the lighting performance of the WLEDs in the near future.